State-of-the-Art Developments of Acoustic Energy Transfer - Md Rabiul Awal; Muzammil Jusoh; Thennarasan Sabapathy; Muhammad Ramlee Kamarudin; Rosemizi Abd Rahim (International Journal of Antennas and Propagation)
Acoustic energy transfer (AET) technology has drawn significant industrial attention recently. This paper presents the reviews of the existing AETs sequentially, preferably, from the early stage. From the review, it is evident that, among all the classes of wireless energy transfer, AET is the safest technology to adopt. Thus, it is highly recommended for sensitive area and devices, especially implantable devices. Though, the efficiency for relatively long distances (i.e., >30 mm) is less than that of inductive or capacitive power transfer; however, the trade-off between safety considerations and performances is highly suitable and better than others. From the presented statistics, it is evident that AET is capable of transmitting 1.068 kW and 5.4 W of energy through wall and in-body medium (implants), respectively. Progressively, the AET efficiency can reach up to 88% in extension to 8.6 m separation distance which is even superior to that of inductive and capacitive power transfer.